EGG PRODUCTION, QUALITY AND CHICK COLOUR PLUMAGE OF FIVE COLOURS OF KAMPONG HENS FED GOOD QUALITY FEED - Mastika, IM; Puger, AW; Budiasa, IKM; Oka, IGL (International Journal of Biosciences and Biotechnology; Vol 1 No 1 (2012), 2013)
An experiment was carried out to study the egg production, quality and chick colour plumage of fi vephenotypic plumage colours of Kampong hens fed good quality feed. A Randomized Block Design consistedof fi ve treatments and fi ve replicateswere used in this experiment. A total of 25 maturated kampong chickensconsisted of fi ve plumage coloursi.e. Black (Selem), Red (biying), Mix colour (brumbun), white plumage withyellow leg (putih siung), and white plumage with white leg (putih kedas) and fi ve cockerels with respectivecolours were used in this experiment. Hens were housed individually in enrich cage. Mating procedurewas done in a special mating cage where each cockerel with respective colour stays all the time. Hen wasbring into the mating cage and left there for 24 hours and repeated after 5 days, until hens were going intobrood. A good quality feed contained 17% CP and 2750 kcal ME were off ered to all hens and fresh waterwere provided ad libitum. Observation was made for 14 weeks.This study showed that in one laying cycleexcept the mixed plumage colour hens produced similar number of eggs while the mix colour was the least.All parameters measured for egg quality from those fi ve plumage colours were similar. Observation ofthe chicks colour at one day old chick (DOC) showed that black plumage, white plumage with yellow leg,and red plumage hens had 100%, 100% and 81% chicks respectively had similar colour to their respectiveparents. While those mix colour and white plumage with white leg were only had 38.89% and 30.2% chickswith similar colour to their respective hens. After 8 weeks old, the colour of the chicks from respectivecolour has changed where black, red, white plumage with yellow leg had 70%, 77.5% and 93.75% chickswith the same colour to their respective hens. While those mix colour and white plumage with white leghad 53.8% and 17.6% chicks with the same colour to their parent. It was concluded that black, red, and whiteplumage with yellow legs had dominant gen in kampong chickens.
Keywords: Kampong chickens, chick colour distribution, egg production, egg quality